Capital Buffer, Risk, Profitability, Size, and Macroeconomics: Empirical Study on Islamic Banks - Septiarini, Dina Fitrisia; Hisan, Ulis Fajar Choirotun; Matsahri, Matsahri; Filianti, Dian (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. The development of Islamic economics has led to the growth of Islamic banking, as a financial institution based on sharia principles. This research aims to analyze the relationship of risk, profitability, company size, and macroeconomics with capital buffer of Shariah Commercial Banks Indonesia during the period of 2015-2019. The study used a quantitative approach of the regression panel data with stata13 statistical tools. This study used secondary data with a population of 14 sharia commercial banks and a sample of 12 Islamic commercial banks using purposive sampling method. BOPO, NM, ROA, and KURS (exchange rate) were found to have significant positive effects on CB. SIZE has a significant negative effect, while NPF has positive  insignificant effect on CB. Islamic banks, regulators, and governments may consider risks, profitability, company size, and macroeconomic conditions in determining the size of capital buffers and maintaining the adequacy of capital owned by Islamic Banking.Abstrak. Ekonomi Islam menjadi paradigma baru yang komprehensif. Bank syariah dalam sistem ekonomi Islam merupakan lembaga keuangan dengan prinsip syariah. Penelitian ini bertujuan untuk menganalisis hubungan risiko, profitabilitas, ukuran perusahaan, dan makroekonomi dengan penyangga modal (CB) Bank umum syariah (BUS) di Indonesia pada tahun 2015-2019. Pendekatan penelitian menggunakan pendekatan data panel kuantitatif regresi dengan alat statistik stata13. Penelitian ini menggunakan data sekunder dengan populasi 14 Bank Islam dan sampel 12 bank umum syariah berdasarkan metode purposive sampling. BOPO, NM, ROA, dan KURS (nilai tukar) ditemukan memiliki pengaruh positif yang signifikan terhadap CB. SIZE memiliki hubungan negatif signifikan, sedangkan NPF positif tidak signifikan. Bank syariah, regulator, dan pemerintah dapat mempertimbangkan risiko, profitabilitas, ukuran perusahaan, dan kondisi makroekonomi dalam menentukan ukuran penyangga modal dan menjaga kecukupan modal yang dimiliki oleh Perbankan Syariah.